What China’s 12th Five-Year Plan Will Mean For Sino-Latin America Relations? - Myers, Margaret (2012)
In March of 2011, China’s National People’s Congress approved the country’s 12th Five-Year Plan, an extensive guide for social and economic planning through the year 2015. Initiated in 1953, China’s five-year plans have laid the foundation for such economic and social movements as the Great Leap Forward, the Cultural Revolution, and the post-Mao era of ‘reform and opening up. ’China’s five-year plans are not reliable predictive tools. Their proposed reforms are ambitious, and their content is as much a policy wish-list as a realistic plan of action. The five-year planning mechanism is useful, however, when identifying those social and economic concerns that the Chinese government considers most relevant to future growth and development. This paper identifies three challenges highlighted in the 12th Five-Year Plan that are likely to be addressed by the Chinese government in coming years. These challenges –economic transformation, resource scarcity, and industry upgrading– and the policies proposed to address them will also play a central role in shaping China’s burgeoning relationship with Latin America, as well as with other regions. Sino-Latin America relations have grown considerably over the past decade, and will continue expanding. China’s successes and failures in addressing its domestic challenges will define its global interests, and shape its course of engagement with Latin America in coming years.